Nanoparticulate Transport of Oximes over an In Vitro Blood-Brain Barrier Model - Wagner, Sylvia; Kufleitner, Jürgen; Zensi, Anja; Dadparvar, Miriam; Wien, Sascha; Bungert, Judith; Vogel, Tikva; Worek, Franz; Kreuter, Jörg; von Briesen, Hagen (PLOS ONE, 2010)
Background Due to the use of organophosphates (OP) as pesticides and the availability of OP-type nerve agents, an effective medical treatment for OP poisonings is still a challenging problem. The acute toxicity of an OP poisoning is mainly due to the inhibition of acetylcholinesterase (AChE) in the peripheral and central nervous systems (CNS). This results in an increase in the synaptic concentration of the neurotransmitter acetylcholine, overstimulation of cholinergic receptors and disorder of numerous body functions up to death. The standard treatment of OP poisoning includes a combination of a muscarinic antagonist and an AChE reactivator (oxime). However, these oximes can not cross the blood-brain barrier (BBB) sufficiently. Therefore, new strategies are needed to transport oximes over the BBB. Methodology/Principal Findings In this study, we combined different oximes (obidoxime dichloride and two different HI 6 salts, HI 6 dichloride monohydrate and HI 6 dimethanesulfonate) with human serum albumin nanoparticles and could show an oxime transport over an in vitro BBB model. In general, the nanoparticulate transported oximes achieved a better reactivation of OP-inhibited AChE than free oximes. Conclusions/Significance With these nanoparticles, for the first time, a tool exists that could enable a transport of oximes over the BBB. This is very important for survival after severe OP intoxication. Therefore, these nanoparticulate formulations are promising formulations for the treatment of the peripheral and the CNS after OP poisoning.